1996
DOI: 10.1093/oxfordjournals.humrep.a019377
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies after intracytoplasmic sperm injection with cryopreserved testicular spermatozoa

Abstract: In 25 patients (14 suffering from obstructive azoospermia, six from non-obstructive azoospermia, three from asthenoazoospermia and two from absence of ejaculation) spermatozoa were extracted from testicular biopsies. Intracytoplasmic sperm injection (ICSI) with fresh testicular spermatozoa was performed in 18 cases; spermatozoa in excess were cryopreserved in pills. No pregnancies were achieved. In the remaining seven patients, testicular spermatozoa were retrieved and cryopreserved during a diagnostic testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 17 publications
4
50
0
3
Order By: Relevance
“…Several studies have reported that the lower number and motility of frozen sperm might affect fertilization and pregnancy rates compared with fresh sperm [25][26][27]. However, no differences in fertilization, embryo cleavage, pregnancy, delivery, and spontaneous abortion rates were reported between fresh and frozen-thawed testicular sperm from men with OA and NOA patients [10,11,30,33]. On the other hand, Palermo et al [34] reported a lower fertilization rate for NOA patients (57 %) compared to OA patients (80 %); however, the clinical pregnancy rate was similar for both patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the lower number and motility of frozen sperm might affect fertilization and pregnancy rates compared with fresh sperm [25][26][27]. However, no differences in fertilization, embryo cleavage, pregnancy, delivery, and spontaneous abortion rates were reported between fresh and frozen-thawed testicular sperm from men with OA and NOA patients [10,11,30,33]. On the other hand, Palermo et al [34] reported a lower fertilization rate for NOA patients (57 %) compared to OA patients (80 %); however, the clinical pregnancy rate was similar for both patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…To date, thousands of live births have been achieved in IVI facilities [24]. Cryopreservation in pellets offers some advantages over other packaging systems.…”
Section: Cryopreservation Of Semen Samplesmentioning
confidence: 99%
“…Cryopreservation in pellets offers some advantages over other packaging systems. These pellets have a higher surface-to-volume ratio with important implications for cooling, freezing and thawing rates of the semen [24,25]. Pellet freezing of domestic animal semen generally produces the best results, but there are commercial pressures to use other methods of packaging [27].…”
Section: Cryopreservation Of Semen Samplesmentioning
confidence: 99%
“…The cryovials was placed in a cryoholders and kept in refrigerator for 15 minutes, then the cryoholders exposed to liquid nitrogen vapor for 10 minutes, before they immersed and kept in liquid nitrogen tank (16) .…”
Section: Process Of Cryopreservationmentioning
confidence: 99%